Wotum Krzysztofa Grzymułtowskiego na sejmie w 1662 roku jako przejaw oratorstwa najwyższej próby - Płachcińska, Krystyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
Parliamentary speeches of the second half of XVIIth century are the the place of inner differentiation in a statement’s style. Besides of the formal style there are some orations, which were created in just forming „average” style and looked almost like a colloquial language. Castellan’s of Poznań, Krzysztof Grzymułtowski’s speeches are the excellent base for studies with this differentiation. The speech in the seym in 1662 is the example of „high-level” style, rich in the applications of rhetorical devices. This kind of style had ussually appeared, when matters seemed hard to the speakers, and it was this case.